Comparative analysis of plasma generated using LIBS technique for different wavelengths of pulsed laser of a cadmium target (Baghdad Science Journal, 2024)
The objective of this study is to analyze the spectral properties of plasma produced from cadmium (Cd) by utilizing the Laser-Induced Breakdown Spectroscopy (LIBS) method. The plasma generation process employed the primary (1064 nm) fundamental harmonic laser (FHL) and the secondary (532 nm) second harmonic laser (SHL) of a Q-switched neodymium-doped laser. Yttrium aluminum Garnet (YAG) is used as a crystalline substance. The laser pulses have a duration of 10 ns, and a repetition rate of 8 Hz and the energy outputs were 250 (mJ) and 500 (mJ) at wavelengths of 1064 (nm) and 532 (nm), respectively. The achievement of precise beam focus was accomplished by focusing the laser onto the target material, which consisted of 100% cadmium. The electron temperature was measured using the Boltzmann plot approach by harnessing empirical data on linear properties associated with neutral lines (Cd II), (O II), (N II), and ion lines (Cd I), (O I)  for (1064, 532) nm. The use of an analytical methodology resulted in the determination of electron temperature values of 8584 K to 15068.4 K for the fundamental and second harmonics of the laser, respectively. Simultaneously, the electron density (ne) was determined by analyzing the Stark broadening profile linked to the neutral cadmium line. The plasma characteristics (electron temperature and electron density) are determined by the modulation of laser energy at the surface of the target, longitudinally along the trajectory of the plasma plume.